Performance of the Freestyle Libre flash glucose monitoring (flash GM) system in individuals with type 1 diabetes: A secondary outcome analysis of a randomized crossover trial - Othmar Moser (Diabetes, Obesity and Metabolism, 2019)
AimsThe efficacy of flash glucose monitoring (flash GM) systems has been demonstrated by improvements in glycaemia; however, during high rates of glucose flux, the performance of continuous glucose monitoring systems was impaired, as detailed in previous studies. This study aimed to determine the performance of the flash GM system during daily‐life glycaemic challenges such as carbohydrate‐rich meals, bolus insulin‐induced glycaemic disturbances and acute physical exercise in individuals with type 1 diabetes.Materials and methodsThis study comprised four randomized trial visits with alternating pre‐ and post‐exercise bolus insulin doses. Throughout the four 14‐hour inpatient phases, 19 participants received three carbohydrate‐rich meals and performed moderate‐intensity exercise. Venous blood glucose and capillary blood glucose during exercise was compared to interstitial glucose concentrations. Flash GM accuracy was assessed by median absolute relative difference (MARD) (interquartile range [IQR]) using the Bland–Altman method and Clark error grid, as well as according to guidelines for integrated CGM approvals (Class II–510(K)).ResultsThe overall MARD (IQR) during inpatient phases was 14.3% (6.9%–22.8%), during hypoglycaemia (≤3.9 mmol/L) was 31.6% (16.2%–46.8%), during euglycaemia (4.0 mmol/L − 9.9 mmol/L) was 16.0% (8.5%–24.0%) and during hyperglycaemia (≥10 mmol/L) was 9.4% (5.1%–15.7%). Overall Bland–Altman analysis showed a bias (95% LoA) of 1.26 mmol/L (−1.67 to 4.19 mmol/L). The overall MARD during acute exercise was 29.8% (17.5%–39.8%), during hypoglycaemia was 45.1% (35.2%–51.1%), during euglycaemia was 30.7% (18.7%–39.2%) and during hyperglycaemia was 16.3% (10.0%–22.8%).ConclusionFlash GM interstitial glucose readings were not sufficiently accurate within the hypoglycaemic range and during acute exercise and require confirmatory blood glucose measurements.